2009
DOI: 10.1097/bor.0b013e3283317b31
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytokines and chemokines in idiopathic inflammatory myopathies

Abstract: The cytokine-chemokine patterns described in recent studies provide further evidence for predominance of Th1-mediated reactions in the different IIMs, inflammation-induced degenerative phenomena in inclusion body myositis, and a possible role for lymphoneogenesis in the sustained inflammatory response in dermatomyositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 35 publications
5
84
0
4
Order By: Relevance
“…42 Analysis of T-cell-receptor molecules expressed by the infiltrating CD8+ T cells reveals clonal expansion of T-cell-receptor chains and conserved sequences in the antigen-binding region, which suggests an antigendriven T-cell response. 43,44 This is further supported by the expression of costimulatory molecules and up-regulation of adhesion molecules, chemokines, and cytokines [45][46][47] (Fig. 2G).…”
Section: Immunopathologymentioning
confidence: 62%
“…42 Analysis of T-cell-receptor molecules expressed by the infiltrating CD8+ T cells reveals clonal expansion of T-cell-receptor chains and conserved sequences in the antigen-binding region, which suggests an antigendriven T-cell response. 43,44 This is further supported by the expression of costimulatory molecules and up-regulation of adhesion molecules, chemokines, and cytokines [45][46][47] (Fig. 2G).…”
Section: Immunopathologymentioning
confidence: 62%
“…These cells putatively induce cytotoxic myonecrosis through an interaction between antigen-presenting MHC-I molecules and co-stimulatory molecules on CD8+ cells [6,17,18]. The infiltrating cells in PM also include CD68+ macrophages and myeloid dendritic cells, which are thought to participate in the cytotoxic process [2,19], as well as apoptosis-resistant CD8+CD28−/−, CD4+ CD28−/−, cells which have been suggested may contribute to treatment resistance [20]. T-cell receptor profiling has shown that the CD8+ T cells are clonally restricted in situ and persist over time [21][22][23].…”
Section: Immunopathogenesis Of Inflammatory Myopathiesmentioning
confidence: 99%
“…Furthermore, the relationship between pregnancy and pathophysiological mechanisms of PM/DM is also unclear (Váncsa et al, 2007), due to extremely limited data. Cytokines and chemokines are essential players in the initiation and progression of the PM/DM, current evidence promoting the predominance of Th1-mediated immunity in different myositis subsets (Aleksza et al, 2005;de Paepe et al, 2009;Szodoray et al, 2010). It has been recently suggested, particularly for patients diagnosed with DM, that the onset of the disease may be triggered by the raise in serum estrogen concentration with subsequent effects on TNFsynthesis as described in early pregnancy (Linardaki et al, 2011).…”
Section: Pm/dm In Pregnancymentioning
confidence: 99%